2023
DOI: 10.1038/s12276-023-00935-z
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 regulates ApoE4-disrupted intracellular lipid homeostasis and decreases synaptic phagocytosis by microglia

Abstract: Although the ε4 allele of the apolipoprotein E (ApoE4) gene has been established as a genetic risk factor for many neurodegenerative diseases, including Alzheimer’s disease, the mechanism of action remains poorly understood. Transient receptor potential vanilloid 1 (TRPV1) was reported to regulate autophagy to protect against foam cell formation in atherosclerosis. Here, we show that ApoE4 leads to lipid metabolism dysregulation in microglia, resulting in enhanced MHC-II-dependent antigen presentation and T-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…CX3CR1 plays a crucial role in regulating the inflammatory response and synapse maturation in CNS microglia ( 122 , 172 , 173 ). During postnatal brain development, the brain participates in synaptic pruning, a natural process in which brain microglia eliminate extra synapses ( 122 , 123 , 133 , 174 , 175 ). Interestingly, despite the relative stability of both Csf1r and Cx3cr1 expression, the fluctuation of their expression levels around 10-fold makes the two genes more suitable for distinguishing microglial subtypes rather than serving as housekeeping biomarkers for microglia ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…CX3CR1 plays a crucial role in regulating the inflammatory response and synapse maturation in CNS microglia ( 122 , 172 , 173 ). During postnatal brain development, the brain participates in synaptic pruning, a natural process in which brain microglia eliminate extra synapses ( 122 , 123 , 133 , 174 , 175 ). Interestingly, despite the relative stability of both Csf1r and Cx3cr1 expression, the fluctuation of their expression levels around 10-fold makes the two genes more suitable for distinguishing microglial subtypes rather than serving as housekeeping biomarkers for microglia ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that the use of the LXR agonist GW3965 can promote the uptake of myelin debris by microglia, reduce lipid droplet formation, and enhance the expression of the cholesterol transporter ABCA1, thereby slowing the progression of Tau protein pathology [ 173 ]. Additionally, the use of capsaicin can rescue lipid metabolism disturbances in ApoE4 neurons, restoring autophagy defects caused by AKT-mTOR pathway disruption [ 174 , 175 ]. Furthermore, research has shown that modulating CYP46A1 with efavirenz enhances cholesterol elimination and circulation in the brain [ 176 ].…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…Jamornwan et al [ 140 ] found that nitro-capsaicin, in both vascular damaged and control microglial cell cultures, suppressed microglial activation, decreasing proinflammatory cytokines, such as TNF-α and IL-6, and enhanced anti-inflammatory factors, such as IL-4 and IL-10. Further, when mice with aberrant e4 apolipoprotein E (ApoE4) genes were given 1 mg/kg/day intraperitoneal capsaicin for 1 month, it reversed impaired lipid metabolism, microglial dysfunction, and other neuronal impairments induced by mutant ApoE4 [ 141 ]. This demonstrates the potential of capsaicin and capsaicin analogues to reduce chronic microglial activation, a risk factor of neurodegenerative disease and cognitive decline.…”
Section: The Effects Of Capsaicin On Cognition and Cerebrovascular Fu...mentioning
confidence: 99%